Systematic significance of cypsela morphology in Lessingianthus (Vernonieae, Asteraceae) - Angulo, Maria Betiana (2015)
The taxonomic significance of cypsela features of South American species of Lessingianthus (Vernonieae,Asteraceae) is analysed for the first time and discussed in relation to other genera of the tribe Vernonieae. The morphology of the cypselae of 112 species of the genus were analysed using stereo-, light and scanning  electron microscopy (SEM) to evaluate the infrageneric relationships and their reliability as taxonomic markers at a generic level. Characters such as cypsela pubescence, carpopodium structure, crystals and idioblasts on the fruit wall were examined. We established three types of cypsela on the basis of the presence or absence, and type of trichomes. Carpopodium is present in all species of the genus. Crystals are very variable in shape and size, with prismatic (rectangular and hexagonal) and styloid shapes. Idioblasts are present in all of the species, except for two. Cypsela features of Lessingianthus are often widespread in other related genera of Vernonieae. Therefore, these characters are not good taxonomic markers at the genus level, but they are valuable within genera to differentiate related species from one another.